PEMBELAJARAN MATEMATIKA MELALUI PENDEKATAN PMRI TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS - Bellinda, Bellinda; Pandra, Viktor; Fauziah, Anna (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
The purpose of this study was to conduct a literatur review related to mathematics learning through the PMRI approach to mathematical understanding abilities. Data collection was carried out by reviewing everything related to learning mathematics using the PMRI method for the 2018-2023 period. The 12 articles used in this study obtained from Harzing Publish or Perish, Google Scholar, and Garuda Kemdikbud. The result of this study indicate that learning mathematics through the PMRI method has improved students understanding.